SISTEM PENGERINGAN IKAN MENGGUNAKAN TENAGA SURYA BERBASIS ARDUINO - Adeh Berydika; Sitohang, Sunarsan (LPPM Universitas Putera Batam, 2022)
ABSTRACT The drying method used by fishermen, especially fishermen in the islands, is still seen using simple technology where some places are not all covered by electricity so that fishermen still use weaving made of bamboo and with fish that have been split to dry quickly and does not cause bacteria. The fish dryer used still depends on weather conditions, which and it takes time to move the drying equipment and the area is quite large to take up a place of 10-20 meters. This drying method which cannot control the thermal conditions in the drying process will cause new bacteria to appear which affect the drying of fish and cannot be kept constant. So that will have an impact on the low quality of fish products produced. Therefore, it is necessary to seek other drying methods that can control bacteria. This study designed a drying system using arduino-based solar power that can control the variables that affect the drying of fish automatically. This tool is very suitable for fishermen to develop fish salting business because it uses solar power